Distribution and abundance of zoeae I (Crustacea, Brachyura) on a coral reef in the southwest Gulf of Mexico - Cházaro-Olvera,Sergio (2020)
Abstract In this study we analyze both seasonal and inter-annual variations in the community parameters of Brachyura zoea I in the Parque Nacional Sistema Arrecifal Veracruzano. Planktonic samples from four transects were collected during three weather conditions: cold fronts; rainy and dry conditions in 2011 and 2012; and cold fronts and dry conditions in 2013. We measured temperature, salinity, and dissolved oxygen, in situ, to determine whether these parameters could explain the observed variations in the community patterns of brachyuran zoea I. We collected zoeae I of 18 species of brachyurans. The dominant species were Libinia dubia H. Milne Edwards, 1834; Menippe nodifrons Stimpson, 1859; and Callinectes sapidus Rathbun, 1896. The temperature and dissolved oxygen were the highest during the rainy conditions and the salinity during the dry conditions in the southern transects. The highest species richness (14) and diversity (2.97 bits individual-1) were found in central transects during cold front conditions. However, we found the highest species richness and diversity during the dry conditions, in the southern transects. Libinia dubia presented the highest density during cold fronts with 1592 ± 127 zoeae 100 m−3 in the northern transect, followed by C. sapidus in the north-central transect, this was observed for both species in the offshore zone. In conclusion, the parameters of the community of zoea I were influenced by the physical parameters measured in each sampling zone.